Pediatric Usher Syndrome Type 2A with Coexisting Rheumatic Heart Disease and Upper Gastro-Intestinal Bleed: A Case Report - Bishal Yadav; Tunam Khadka; Toyendra Jung Shah; Mandish Prasad Phuyal; Rajesh Lamichane; Bikash Chaurasiya (Journal of Nepal Medical Association)
Usher syndrome is a rare autosomal recessive disorder characterized by progressive sensorineural hearing loss and retinitis pigmentosa, typically present from birth and later symptoms, including loss of night vision and peripheral vision slowly progressing to blindness. The condition exhibits clinical and genetic diversity and currently lacks the definitive treatment. This report presents a case of a ten-year-old female diagnosed with Usher syndrome type IIA via whole exome sequencing. The delayed onset of visual symptoms often leads to a misdiagnosis to isolated deafness in early years. The early identification allows for better prognosis through surveillance and intervention in hearing and visual impairments. If usher patients can receive a timely diagnosis, genetic molecular therapies may help preserve the photoreceptors, subsequently development of blindness could be delayed or possibly be prevented.